Practical exercise advice during pregnancy - Weiss Kelly, A. K. (The Physician and Sportsmedicine, 2005)
Many women enjoy regular exercise as a part of a healthy lifestyle and may wish to continue exercising after they become pregnant. Some previously sedentary women may want to start an exercise program during pregnancy. Primary care and sports medicine physicians should understand the contraindications (eg, hypertension, diabetes, placenta previa, preeclampsia) and the concerns about exercise during pregnancy (eg, fetal nutrition, risk of preterm labor) and be able to offer reasonable guidelines to women who wish to start or continue exercise during pregnancy. Most non-weight-bearing exercises (eg, swimming, stationary bicycling) and walking are safe for pregnant women, beginning with 15 minutes of exercise three times a week and progressing as tolerated.